Meningkatkan Kemampuan Menulis Resume Diskusi melalui Metode PBL pada Siswa Kelas IX MTs Negeri 1 Madiun - Nanik Sulistyani (Tamilis Synex: Multidimensional Collaboration, 2025)
The purpose of this study was to improve the ability to write discussion resumes of grade IX students of MTs Negeri 1 Madiun through the application of the PBL method. This study used the Classroom Action Research (CAR) method to improve the ability to understand reading fiction books of grade IX students at MTs Negeri 1 Madiun, which was carried out in two cycles with four phases: planning, implementation, observation, and reflection. Each cycle aims to evaluate the effectiveness of actions in improving students' reading skills, which are measured by increasing students' completeness in understanding and writing fiction book resumes. The results of the evaluation were analyzed using the Miles and Huberman interactive analysis model, with the absorption formula to determine the level of student success categorized in the learning completeness criteria. The results showed that the application of the PBL method was able to improve the ability to write discussion resumes of grade IX students of MTs Negeri 1 Madiun. Students' learning completeness increased from 40.63% in the pre-cycle to 71.88% in cycle I, and reached 93.75% in cycle II. PBL encourages students' active participation in discussions, critical thinking, and improves collaborative and communication skills.